PERANAN METODE CERAMAH DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VI PADA BIDANG STUDI PENDIDIKAN AGAMA ISLAM DI SD AL-MUZZAMMIL BEKASI - Zainal Muttaqin (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2018)
Methods in the process of education is one of the important things that contribute to determine the success of teachers to students in achieving teaching objectives. A teacher can be classified success in teaching if he / she uses a good method and appropriate to the student's needs. To strive the islamic religious education can be accepted by learners, then a teacher must use appropriate methods and in accordance with the situation and conditions. In this case the teacher can use several methods depending on the material to be delivered and the condition of the learners themselves. The compatible between the subject matter and the method and application of the method is very important. It is intended to avoid the failure in achieving the educational goals outlined on each subject. Therefore a teacher needs to find and narrate which method is more appropriate to apply in teaching. The purpose of this study is to determine whether there is the role of lecture methods in improving the sixth grade students’learning achievement of in the field of Islamic Religious Education in ALMuzzammilElementary School Bekasi. The method used in this research is descriptive method that that tells, analyzes, and classifies with survey technique, interview, questionnaire, observation, documentation or with test and data processing technique using percentage. While the interpretation of the data is to determine the scale of calculation from 1% to 100% as follows: 61% to 99% stated most, 51% to 60% stated more than half, 50% stated half, 40% to 49% stated almost half, 1% to 39% stated a small part, and 0% stated none at all.After the data collected, then processed, analyzed and concluded. From the results of the research, it is known that 85% of teachers of Islamic religious education always use lecture method, 75% of students like the lecture method in learning, 65% of students can easily understand the lesson of PAI by lecture method, 75% of students find no difficulty in understanding the words or speech of PAI teacher with the use of lecture method, 90% with lecture method of student achievement there is improvement. From the results of this study, the authors can take one conclusion that "Lecture Method plays a role in improving student achievement in the Islamic religious education".